National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 3 NATIONAL HEALTH SERVICE BILL SUMMARY OF THE PROPOSED NEW SERVICE This paper contains a general description of the proposed health service with which the Bill deals. It is intended only as a factual summary, omitting comment or argument. Moreover, being only a general summary, it cannot always be in precise terms and it is to the Bill itself, not this paper, that anyone must look for more exact definition of what is proposed. INTRODUCTORY 1. The Bill provides for the establishment of a comprehensive health service in England and Wales. A further Bill to provide for Scotland will be introduced later. 2. The Bill does not deal in detail with everything involved in the service. It deals with the main structure. Within that structure, further provision will be made by statutory regulations — on lines which the Bill lays down and subject always to the control of Parliament. Scope of the service 3. The Bill provides for the following kinds of health services:— (i) Hospital and specialist services — i.e. all forms of general and special hospital provision, including mental hospitals, together with sanatoria, maternity accommodation, treatment during convalescence, medical rehabilitation and other institutional treatment. These cover in-patient and out-patient services, the latter including clinics and dispensaries operated as part of any specialist service. The advice and services of specialists of all kinds are also to be made available, where necessary, at Health Centres and in the patient's home. (ii) Health Centres and general practitioner services — i.e. general personal health care by doctors and dentists whom the patient chooses. These personal practitioner services are to be available both from new publicly equipped Health Centres and also from the practitioners' own surgeries. (iii) Various supplementary services — including midwifery, maternity and child welfare, health visiting, home-nursing, a priority dental service for children and expectant and nursing mothers, domestic help where needed on health grounds, vaccination and immunisation against infectious diseases, additional special care and after-care in cases of illness, ambulance services, blood transfusion and laboratory services. (Special school health services are already provided for in the Education Act of 1944.) (iv) The provision of spectacles, dentures and other appliances, together with drugs and medicines — at hospitals, Health Centres, clinics, pharmacists' shops and elsewhere, as may be appropriate. Availability of the service 4. All the service, or any part of it, is to be available to everyone in England and Wales. The Bill imposes no limitations on availability — e.g. limitations based on financial means, age, sex, employment or vocation, area of residence, or insurance qualification. 5. The last is important. If the National Insurance Bill now before Parliament is passed into law, almost everyone will become compulsorily insurable, and after payment of the appropriate contributions will become entitled to 292/847/4/115